Nanotechnology Role for the Production of Clean Fuel E-85 and Petrochemical Raw Materials - Iskander K. Basily; Amira L. Shafik; Ali A. Sarhan; Mona B. Mohamed (Journal of Nanotechnology)
There have been a number of substantive technical changes that can be described as revolutionary process and evolutionary process. One of these approaches is the use of nanotechnology in the two-stage pyrolysis of petroleum residues of the heavy distillates separated from the Arabian crude oil. Two-stage catalytic pyrolysis technique proved to be an excellent method for the production of unsaturated hydrocarbons (which easily can be converted to alcohol, by addition of H2O, for the production of E-85, i.e., clean fuel) regardless the type of feed stocks used. Basically, the catalysts are arranged into three large groups; amorphous and crystalline alumino-silicates, alkaline or alkaline earth alumino compounds, and different metal oxides on different catalyst carriers such as Zeolites. The high yield of ethylene (30–40%) brought by different catalysts at temperatures of 700–750°C appear to justify the intensive research work in this field.